Generación de contenidos digitales para la reactivación del patrimonio arquitectonico. Estudio de caso: plaza de mercado de techo cubierto de Guayaquil, Medellín (2014)
Thanks to own technological resources and the convergence of media such as interactive texts, data that allow tactile navigation, maps, planes, images, and virtual models, among others, the material patrimony can be celebrated, contemplated, and admired just by pushing a key. Graphic recreation of a historical building, such as “Plaza de Mercado de Techo Cubierto de Guayaquil,” study case of this research and city site colloquially known as “Plaza Cisneros de Medellin,” was a social milestone of the nineteenth century, since places around this building were the scenarios of marketing and transportations movements in Medellin. For this reason, and thanks to the technology known as Augmented Reality (AR) and the creation of digital contents provided in the research, personalization of information related to cultural patrimony ca be achieved, as well as its handling through mobile devices as mass communication tools by means of which several audiences access contents, navigation routines, and digital information consumption, entertainment experiences, online networking through communication services